A toolkit for supporting evaluation - Gráinne Conole; Ed Crew; Martin Oliver; Jen Harvey (Association for Learning Technology, 2001)
Despite the current consensus that adapting and reusing existing learning resources, including Information and Communication Technology (ICT), is a good thing, examples of this practice are few and far between. This can be traced to a number of factors. In particular, the 'not invented here' syndrome (HEFCE, 1996) is no doubt still present. However, more important is the issue of the time and skills required to retrieve, evaluate and then adapt materials. This is compounded by the fact that identifying suitable resources in the first place can be complex (although the growth of subject-specific information gateways, portals and guidelines to resources will go some way towards alleviating this problem).